Comparing simulated and observed EMIC wave amplitudes using in situ Van Allen Probes' measurements. (October 2018) - Saikin, A.A.; Jordanova, V.K.; Zhang, J.C.; Smith, C.W.; Spence, H.E.; Larsen, B.A.; Reeves, G.D.; Torbert, R.B.; Kletzing, C.A.; Zhelavskaya, I.S.; Shprits, Y.Y.
Abstract: We perform a statistical study calculating electromagnetic ion cyclotron (EMIC) wave amplitudes based off in situ plasma measurements taken by the Van Allen Probes' (1.1–5.8 Re ) Helium, Oxygen, Proton, Electron (HOPE) instrument. Calculated wave amplitudes are compared to EMIC waves observed by the Electric and Magnetic Field Instrument Suite and Integrated Science on board the Van Allen Probes during the same period. The survey covers a 22-month period (1 November 2012 to 31 August 2014), a full Van Allen Probe magnetic local time (MLT) precession. The linear theory proxy was used to identify EMIC wave events with plasma conditions favorable for EMIC wave excitation. Two hundred and thirty-two EMIC wave events (103 H + -band and 129 He + -band) were selected for this comparison. Nearly all events selected are observed beyond L = 4. Results show that calculated wave amplitudes exclusively using the in situ HOPE measurements produce amplitudes too low compared to the observed EMIC wave amplitudes. Hot proton anisotropy ( A hp ) distributions are asymmetric in MLT within the inner ( L < 7) magnetosphere with peak (minimum) A hp, ∼0.81 to 1.00 (∼0.62), observed in the dawn (dusk), 0000 < MLT ≤ 1200 (1200 < MLT ≤ 2400), sectors. Measurements of A hp are found to decrease in the presence of EMIC wave activity. A hp amplification factors are determined and vary with respect to EMIC wave-band and MLT. He + -band events generally require double (quadruple) the measured A hp for the dawn (dusk) sector to reproduce the observed EMIC wave amplitudes. Highlights: In situ plasma measurements cannot reproduce observed EMIC wave amplitudes. Inner magnetosphere A hp distributions are asymmetric in MLT. A hp decreases in the presence of EMIC waves. A hp provides more "free energy" than A hhe or A ho . A hp must be increased (2–4 times measured value) to replicate EMIC wave amplitudes.